PERKEMBANGAN KONVERSI LAHAN PERTANIAN DI BAGIAN NEGARA AGRARIS - Qurotu Ayun; Shidiq Kurniawan; Wahyu Adhi Saputro (JURNAL VIGOR, 2020)
Conversion of agricultural land is rife in agricultural countries like Indonesia, especially in areas bordering cities. Transfer of agricultural land functions is inevitable because of the welfare of farmers who are still neglected. This study aims to determine 1) the conversion of agricultural land to non-agricultural 2) determine the impact of the conversion of agricultural land. The research method used is descriptive analytic method. The data used is secondary data from the Indonesian Central Statistics Agency and the Land Agency. The data analysis method uses the net land conversion method. The data used is time series data. The location selection is purposive sampling based on the area bordering urban areas, namely Grogol Subdistrict, Sukoharjo Regency. Based on the results and discussion above, it can be concluded that the net land conversion is still negative in Grogol District, which means that the area of converted agricultural land is greater than the new paddy field mold. The positive impacts generated such as the availability of residential land for the community, the availability of new housing with relatively cool air, the existence of even distribution of the population and the development of the potential of the area that was previously minimal population. However, the negative impacts caused are more crucial, such as the reduction of food resources and water reserves, the change in the profession of the community, which initially farmers became factory workers, service sectors and others, reduced ecosystems and began to contaminate land, water and air from the activities of surrounding communities.  Keywords: Agraris, Conversion, Land, Agriculture Impact